Parasitic infections in ornamental cichlid fish in the Peruvian Amazon - Aguinaga, Jefferson Yunis [UNESP]; Marcusso, Paulo Fernandes [UNESP]; Claudiano, Gustavo da Silva [UNESP]; Marotta, Bruno L. [UNESP]; Sebastiao, Fernanda de Alexandre [UNESP]; Kochenborger Fernandes, Joao Batista [UNESP]; Moraes, Flavio Ruas de [UNESP]; Engracia de Moraes, Julieta Rodini [UNESP] (Brazilian Coll Veterinary Parasitology, 2015)
The aim of this study was to evaluate the prevalence and seasonal distribution of the main parasite species in Amazonian ornamental cichlids that affect their trade. The study was conducted from August 2007 to September 2009. We sampled 3042 specimens from 9 different species, of which 9.47% had at least one type of external parasite. 81.25% of the cases occurred in the dry season. Crenicichla anthurus (28.57%) was the most parasitized, followed by Aequidens diadema (26.32%), Pterophyllum scalare (22.69%), Cichlasoma sp. (9.52%), Apistogramma sp. (3.88%) and Symphysodon aequifasciatus (3.66%). Monogenea was the most abundant group of parasites, occurring in 66.67% of the cases, of which 96.88% occurred in the dry season. This parasite infested 95.68% of Pterophyllum scalare, 76.67% of Apistogramma sp, 33.33% of Cichlasoma sp. and 23.81% of Symphysodon aequifasciatus cases. Ichthyophthirius multifiliis infested 100% of Aequidens diadema, 76.19% of Symphysodon aequifasciatus, 66.67% of Cichlasoma sp, 41.67% of Crenicichla anthurus and 23.33% of Apistogramma sp cases. Myxosporidia infested 58.33% of Crenicichla anthurus. Trichodina infested 4.32% of Pterophyllum scalare. The prevalence of these parasites is related to the season, preferred habitat, fish behavior, individual susceptibility and handling of animals during transportation by fishermen.

O objetivo deste estudo foi avaliar a prevalência e distribuição sazonal das principais espécies de parasitas em ciclídeos ornamentais amazônicos que afetam seu comércio. O estudo foi realizado entre agosto de 2007 e setembro de 2009. Foram amostrados 3042 espécimes de 9 espécies diferentes, das quais 9,47% tinham pelo menos um tipo de parasita externo. Na estação seca, ocorreram 81,25% dos casos. Crenicichla anthurus (28,57%) foi o mais parasitado, seguido por Aequidens diadema (26,32%), Pterophyllum scalare (22,69%), Cichlasoma sp. (9,52%), Apistogramma sp. (3,88%), e Symphysodon aequifasciatus (3,66%). Monogenea foi o grupo mais abundante de parasitas, ocorrendo em 66,67% dos casos. Na estação seca, ocorreram 96,88% deles. Este parasita infestou 95,68% dos casos em Pterophyllum scalare, 76,67% em Apistogramma sp., 33,33% em Cichlasoma sp. e 23,81% em Symphysodon aequifasciatus. Ichthyophthirius multifiliisinfestou 100% dos casos em Aequidens diadema, 76,19% em Symphysodon aequifasciatus, 66,67% em Cichlasoma sp., 41,67% em Crenicichla anthurus e 23,33% em Apistogramma sp.; Myxosporidia infestou 58,33% dos casos em Crenicichla anthurus; Trichodina infestou 4,32% dos casos em Pterophyllum scalare. A prevalência desses parasitas está relacionada com a época do ano, hábitat preferido, comportamento dos peixes, suscetibilidade individual e manejo dos animais durante o transporte pelos pescadores.
Infestação parasitária em ciclídeos ornamentais da Amazônia de Peru
Keywords: Ornamental fish; Cichlid; parasites; Amazon; Peixes ornamentais; Cichlidae; Parasitas; Amazônia